Risk of surgery for subacromial impingement syndrome in relation to neck-shoulder complaints and occupational biomechanical exposures: a longitudinal study - Svendsen, Susanne Wulff; Dalbøge, Annett; Andersen, Johan Hviid; Thomsen, Jane Frølund; Frost, Poul (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'The aim of this longitudinal study was to evaluate the risk of surgery for subacromial impingement syndrome (SIS) in relation to neck-shoulder complaints and occupational biomechanical shoulder exposures. ' ' METHODS ': 'The study was based on the Musculoskeletal Research Database at the Danish Ramazzini Centre. We linked baseline questionnaire information from 1993–2004 on neck-shoulder complaints, job titles, psychosocial work factors, body mass index, and smoking with register information on first-time surgery for SIS from 1996–2008. Biomechanical exposure measures were obtained from a job exposure matrix based on expert judgment. We applied multivariable Cox regression. ' ' RESULTS ': 'During 280 125 person-years of follow-up among 37 402 persons, 557 first-time operations for SIS occurred. Crude surgery rates increased from 1.1 to 2.5 per 1000 person-years with increasing shoulder load. Using no neck-shoulder complaints and low shoulder load at baseline as a reference, no neck-shoulder complaints and high shoulder load showed an adjusted hazard ratio (HRadj) of 2.55 [95% confidence interval (95% CI) 1.59–4.09], while neck-shoulder complaints in combination with high shoulder load showed an HRadj of 4.52 (95% CI 2.87–7.13). Subanalyses based on 18 856 persons showed an HRadj of 5.40 (95% CI 2.88–10.11) for complaints located specifically in the shoulder in combination with high shoulder load. ' ' CONCLUSIONS ': 'Based on these findings, persons with neck-shoulder and especially shoulder complaints in combination with high shoulder load seem an obvious target group for interventions aimed at reducing exposures to prevent surgery for SIS.
Keywords: acromioplasty; force; job exposure matrix; job strain; longitudinal study; neck-shoulder complaint; occupation biomechanical exposure; posture; psychosocial factor; repetitive work; shoulder; subacromial decompression; subacromial impingement syndrome; surgery; work